PENDIDIKAN SEKOLAH DASAR 2024; MENYIAPKAN GENERASI EMAS DENGAN KETERAMPILAN ABAD 21 - Moh Pudali Arodani; Misriyani; Fardan Firdausy; Mas odi (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Primary School (SD) education in 2024 aims to prepare the young generation who are able to compete and innovate in the ever-growing digital era. The "Golden Generation" which is the nation's hope must be equipped with 21st century skills, such as critical thinking, creativity, collaboration, communication, and adequate digital literacy. With the implementation of the Merdeka Curriculum, education at the elementary level places more emphasis on developing students' individual potential, providing space for more flexible learning, and focusing on skills that are relevant to the needs of the world of work in the future. Additionally, technology plays an important role in supporting learning, enabling students to access digital resources, collaborate online, and develop necessary technical skills. This article examines the importance of implementing 21st century skills in elementary education, the challenges in implementing appropriate education policies, and the role of technology in enriching students' learning experiences. Holistic education, including the development of students' social and emotional intelligence, is an important foundation for forming a generation that not only excels in academics, but also has strong character.